Liver Transplantation without Perioperative Transfusions Single-Center Experience Showing Better Early Outcome and Shorter Hospital Stay - Nicolás Goldaracena; Patricio Méndez; Emilio Quiñonez; Gustavo Devetach; Lucio Koo; Carlos Jeanes; Margarita Anders; Federico Orozco; Pablo D. Comignani; Ricardo C. Mastai; Lucas McCormack (Journal of Transplantation)
Background. Significant amounts of red blood cells (RBCs) transfusions are associated with poor outcome after liver transplantation (LT). We report our series of LT without perioperative RBC (P-RBC) transfusions to evaluate its influence on early and long-term outcomes following LT. Methods. A consecutive series of LT between 2006 and 2011 was analyzed. P-RBC transfusion was defined as one or more RBC units administrated during or ≤48 hours after LT. We divided the cohort in “No-Transfusion” and “Yes-Transfusion.” Preoperative status, graft quality, and intra- and postoperative variables were compared to assess P-RBC transfusion risk factors and postoperative outcome. Results. LT was performed in 127 patients (“No-Transfusion” = 39 versus “Yes-Transfusion” = 88). While median MELD was significantly higher in Yes-Transfusion (11 versus 21; P=0.0001) group, platelet count, prothrombin time, and hemoglobin were significantly lower. On multivariate analysis, the unique independent risk factor associated with P-RBC transfusions was preoperative hemoglobin (P<0.001). Incidence of postoperative bacterial infections (10 versus 27%; P=0.03), median ICU (2 versus 3 days; P=0.03), and hospital stay (7.5 versus 9 days; P=0.01) were negatively influenced by P-RBC transfusions. However, 30-day mortality (10 versus 15%) and one- (86 versus 70%) and 3-year (77 versus 66%) survival were equivalent in both groups. Conclusions. Recipient MELD score was not a predictive factor for P-RBC transfusion. Patients requiring P-RBC transfusions had worse postoperative outcome. Therefore, maximum efforts must be focused on improving hemoglobin levels during waiting list time to prevent using P-RBC in LT recipients.